The boundaries of blame: towards a universal partial defence for the criminal law - Kennefick, Louise (Cambridge University Press, 2025)
"Brings social justice to criminal responsibility through a 'real person' approach to blaming people. It is essential reading for researchers and scholars of criminal law and justice across common law jurisdictions. It appeals to general readers interested in reform, proposing how law can blame in a fairer way"--